Heterosis and combining ability estimate on yield and yield-related traits in a half diallel crosses of kenaf (Hibiscus cannabinus L.) in Malaysia - Al-Mamun, Md; Rafii, Mohd Y.; Misran, Azizah; Berahim, Zulkarami; Ahmad, Zaiton; Hasan Khan, Md Mahmudul; Oladosu, Yusuff (Taylor and Francis Group, 2023)
Understanding heterosis and combining ability among distinct kenaf (Hibiscus cannabinus L.) genetic resources is crucial for developing hybrid kenaf. An investigation was conducted on 36 F1 combinations produced from nine parental genotypes of kenaf in a diallelic scheme using Griffing diallel analysis technique 2, model I. Highly significant F-test values revealed the presence of variability for all the 15 quantitative traits for general combining ability (GCA) and specific combining ability (SCA) except days to 1st flowering. The magnitude of GCA variance was considerably higher than that of SCA variance for plant height, stem middle diameter, stem top diameter, days to flowering, number of pods, number of seeds and 1000 seeds weight, showing the predominates of additive gene for these traits. Narrow-sense heritability of 50.93% in the combined environments showed that seed number was the most heritable trait, whereas days to 1st flowering and 1000 seed weight had moderate heritability. Parents P1, P3 and P4 had the most dominant alleles for most traits studied. Considering SCA and heterosis values, the hybrids H3, H4, H9, H11, H23, H29 and H35 had high heterotic for fiber and seed yield.